The municipalities’ environmental situation assessment as a basis for customizing strategies - P. S. Trifonova (Вестник университета, 2022)
The article reveals the issues of assessing the ecological situation of municipalities. Based on an analysis of the socio-economic development strategies of municipalities in the Sverdlovsk region, it has been concluded that they lack the disclosure of the strategic direction “Ecology” in them, which can become the basis for the individualization of strategies. The article presents the author’s approach to assessing the tension of the ecological situation of the territories, which makes it possible to identify the most acute environmental problems. A multi-stage algorithm for calculating a complex and integral indicator of the intensity of the ecological situation of territories is proposed. The approach has been tested in three municipalities of the Gornozavodsk administrative district in the Sverdlovsk region. It has been concluded that the environmental situation in the Gornozavodsky administrative district is primarily determined by the industrial nature of activities and, consequently, by high levels of atmospheric air and water pollution.